Spontaneous poisoning by Palicourea marcgravii (Rubiaceae) in a sheep herd in southeastern Brazil - Koether, Karoline [UNESP]; Lee, Stephen T.; Belluci, Renata S. [UNESP]; Garcia, Rodrigo [UNESP]; Pfister, James A.; Cunha, Paulo Henrique J.; Rocha, Noeme S. [UNESP]; Borges, Alexandre S. [UNESP]; Oliveira-Filho, Jose P. [UNESP] (Elsevier, 2019)
Palicourea marcgravii (Rubiaceae) is considered the most important toxic plant affecting livestock farming in Brazil. This study describes an outbreak of spontaneous poisoning by P. marcgravii in sheep. Forty-nine sheep died while showing clinical signs of sudden death after having access to the plant. During the necropsy, P. marcgravii leaves were observed in the rumens of the animals. Histopathological analysis demonstrated hydropic degeneration of the kidneys. Monofluoracetate concentration obtained in Palicourea samples was 0.53% (5.3 μg/mg). These findings collectively indicate that the affected animals died from poisoning due to P. marcgravii.
Keywords: Monofluoracetate; Palicourea; Poisoning; Sheep; Sudden death